2022
DOI: 10.1007/s00127-022-02330-x
|View full text |Cite
|
Sign up to set email alerts
|

Calls to the anti-violence number in Italy during COVID-19 pandemic: correlation and trend analyses of violence reports during 2020

Abstract: Purpose We hypothesized that during the 2020 pandemic there has been a significant change along the year, depending on the SARS-CoV-2 impact on the population and varying difficulties implied in the norms that were adopted to embank the pandemic. Our objectives were to verify how the phenomenon of domestic violence has evolved and changed along 2020, and to clarify if these changes were correlated to the evolution of the pandemic. Methods Though the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…Contrary to what was found in 2020 [23], DD was not significantly related to the daily number of calls in 2021. It could be hypothesized that, during 2020, the number of deaths indicated the severity of the pandemic, as it was at the center of media communication, explaining the established containment measures, such as the lockdown period, but in 2021 the number of deaths was not a criterion for the transition of the Italian Regions' status from one color to another, and therefore not directly influential on the risk of being in a region with more restrictive measures, which entailed a greater compulsory stay at home.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to what was found in 2020 [23], DD was not significantly related to the daily number of calls in 2021. It could be hypothesized that, during 2020, the number of deaths indicated the severity of the pandemic, as it was at the center of media communication, explaining the established containment measures, such as the lockdown period, but in 2021 the number of deaths was not a criterion for the transition of the Italian Regions' status from one color to another, and therefore not directly influential on the risk of being in a region with more restrictive measures, which entailed a greater compulsory stay at home.…”
Section: Discussioncontrasting
confidence: 99%
“…Thanks to this number, women who suffer violence can receive support at various levels. As for 2020, previous research has already investigated the phenomenon of domestic violence reports from women during the 2020 pandemic in Italy [ 23 ], finding that the number of daily calls from women to NAN was positively correlated with the trend of the pandemic (COVID-19 daily deaths, daily hospitalizations, daily home quarantined, and daily home quarantined postponed by 30 days). However, there is no analysis of violence episodes in 2021, the year in which the scenario changed.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence is even more important in the current historical phase, in which, favored by the psychological and sociological impact of the COVID 19 pandemic (Benfante et al, 2022; Blasco-Belled et al, 2022; Zara et al, 2021), IPV episodes have increased exponentially (Barbara et al, 2022; Barchielli et al, 2021; Brink et al, 2021; Del Casale et al, 2022; Romito et al, 2022). As in many other areas, interventions, including psychological interventions, to prevent and manage IPV are not only necessary but due.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported increased addictive disorders during the COVID-19 quarantine, such as internet addiction, online gambling, pornography, alcoholism, or drug misuse among the general population [34][35][36]. Home isolation restricted family members to their residences, aggravated household conflicts, and increased domestic violence and child maltreatment [37][38][39][40]. Meanwhile, survivors of COVID-19 experienced post-traumatic stress disorder (PTSD) with disproportionately elevated symptoms among those requiring inpatient admission, ventilation support, and treatment for pre-existing mental disorders [41,42].…”
Section: Introductionmentioning
confidence: 99%